The ParaView Coprocessing Library: A scalable, general purpose in situ visualization library - Fabian, N.; Moreland, K.; Thompson, D.; Bauer, A. C.; Marion, P.; Gevecik, B.; Rasquin, M.; Jansen, K. E. (2011 IEEE Symposium on Large Data Analysis and Visualization, 2011)
As high performance computing approaches exascale, CPU capability far outpaces disk write speed, and in situ visualization becomes an essential part of an analyst's workflow. In this paper, we describe the ParaView Coprocessing Library, a framework for in situ visualization and analysis coprocessing. We describe how coprocessing algorithms (building on many from VTK) can be linked and executed directly from within a scientific simulation or other applications that need visualization and analysis. We also describe how the ParaView Coprocessing Library can write out partially processed, compressed, or extracted data readable by a traditional visualization application for interactive post-processing. Finally, we will demonstrate the library's scalability in a number of real-world scenarios.